Skip to content
Related Articles

Related Articles

ISRO | ISRO CS 2016 | Question 13
  • Last Updated : 20 Nov, 2018

The simplified SOP (Sum of Product) form the Boolean expression (P + Q’ + R’)(P + Q + R)(P + Q + R’)

(A) (P’Q + R)
(B) (P + QR’)
(C) (P Q’ + R )
(D) (PQ + R)


Answer: (B)

Explanation: for given expression, (P + Q’ + R’)(P + Q + R)(P + Q + R’)
=P + PQ + PR + PQ’ + Q’R + PR’ + R’Q) (P + Q + R’) // Since, (P + PQ) = P(1 + Q) = P
=(P + Q’R + QR’)(P + Q + R’)
=(P + PQ + PR’ + PQ’R + PQR’ + QR’)
=(P + QR’)

Quiz of this Question

My Personal Notes arrow_drop_up
Recommended Articles
Page :